2022
DOI: 10.54117/gjpas.v1i2.42
|View full text |Cite
|
Sign up to set email alerts
|

Ab’initio studies of the structural and electronic properties for single-walled armchair MgONT, SiCNTs and ZnONTs for next generations’ optoelectronics

Abstract: Due to greater demand to use 1D semiconducting chips to replace semiconductors made from bulk structures We studied the structural and electronic properties of free (7, 0) metallic oxides and non-metallic carbide nanotubes. SWMgONT, SWZnONT and SWSiCNT were chosen as the representative model. All the quantum simulation studies were done within DFT ab’initio implemented in quantum ESPRESSO. Results obtained for structural properties revealed that the most stable bond lengths of MgONT, ZnONT and SiCNT are 1.80 Å… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…The efficiency rate of photocatalysts depends on their light absorption properties which are dependent on the imaginary dielectric constant. 20 We define the optical response of photocatalyst materials to the incident solar radiation in terms of the real and imaginary dielectrics as 21 ε ( ω ) = ε 1 ( ω ) + ε 2 ( ω )where ε 1 ( ω ) is the real part and ε 2 ( ω ) is the imaginary part of the optical dielectric constant. The real part of the dielectric function takes care of the photon energy dispersion, while the imaginary part of the dielectric function describes the photon energy absorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency rate of photocatalysts depends on their light absorption properties which are dependent on the imaginary dielectric constant. 20 We define the optical response of photocatalyst materials to the incident solar radiation in terms of the real and imaginary dielectrics as 21 ε ( ω ) = ε 1 ( ω ) + ε 2 ( ω )where ε 1 ( ω ) is the real part and ε 2 ( ω ) is the imaginary part of the optical dielectric constant. The real part of the dielectric function takes care of the photon energy dispersion, while the imaginary part of the dielectric function describes the photon energy absorption.…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency rate of photocatalysts depends on their light absorption properties which are dependent on the imaginary dielectric constant. 20 We dene the optical response of photocatalyst materials to the incident solar radiation in terms of the real and imaginary dielectrics as 21…”
Section: Optical Absorptionsmentioning
confidence: 99%
“…Although both results fall within the band gap range of the photocatalyst, the GGA value was an underestimate, while the G 0 W 0 value gives the exact band gap obtained. Furthermore, the band gap obtained is direct since VBM and CBM all have the same momentum . As can be seen, the CBMs of the MoS 2 -doped SWBNNT are larger than the H + /H 2 potential (−4.40 eV), so they are suitable photocatalysts for the half-reaction of hydrogen reduction .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the band gap obtained is direct since VBM and CBM all have the same momentum. 27 As can be seen, the CBMs of the MoS 2 -doped SWBNNT are larger than the H + /H 2 potential (−4.40 eV), so they are suitable photocatalysts for the half-reaction of hydrogen reduction. 28 Based on the obtained results, it can be shown that the (12,12) MoS 2 -doped SWBNNT semiconductor can be an excellent candidate for enhanced photocatalytic water splitting.…”
Section: Effects Of Mos 2 Doping On the Electronic (Photocatalytic) P...mentioning
confidence: 97%
“…Te quasi-particle band gaps are formed from the weak interactions of SWCNT and SWBNNT atoms which are renormalized to smaller values in the presence of dielectric substrates of boron nitride nanotubes [22]. Te narrowing of the band gap is due to the polarization-induced screening efects which change the correlation energy of the SWCNT orbitals which stabilizes the valence band [23].…”
Section: Electronic Transport Of Dwcbnntmentioning
confidence: 99%